The level of information held by a problem solver influences decision processes - LONGO, Angelarosa; VENTRE, Viviana (Journal of Mathematical Economics and Finance; Vol 2 No 1 (2016): Volume II Issue 1(2) Summer 2016, 2016)
Traditional Discounted Utility Model (DU model) fails to explain human behav- ior for intertemporal choice, because Rational models in decision processes are marked out by many anomalies: individual choices are strictly influenced by cognitive and motivational biases which can be different among people and for each person in different situation. The difference in the effects (positives and negatives) of emotions and impulsivity, and the conse- quent inconsistent preferences, are mainly linked to mental models of each person. We point out that the level of information of each problem solver plays an important role in causing inconsistent preferences: in a single or multi agent decision process each mental model is influenced by the presence, the absence or the inconsistency of information about the problem or about other members of the decision making group. We demonstrate that only about strict conditions decision models coincide with real choices, because only in particular cases the opti- mum and rational decision matches with the real one. The difficulty in modeling these effects is even greater because behavioral biases influence also the modeler. Behavioral Operational Research (BOR) studies these influences to create efficient models to define choices in similar decision processes.